Selfish Node Detection for Effective Data Transmission Using Modified Incentive Sorted Pathway Selection in Wireless Sensor Networks. (18th February 2022) - Ashok Babu, P.; Kavisankar, L.; Xavier, Jasmine; Senthilkumar, V.; Kumar, Gokul; Kavitha, T.; Rajendran, A.; Harikrishnan, G.; Rajaram, A.; Adigo, Amsalu Gosu
Abstract : Wireless nodes have time-varying behavior in their nature because the energy usage of each node is not being constant. Packet transmission among cluster nodes gets overloaded when multi-input and multioutput is made; multitask is performed causing more energy usage; also, selfish node could not transfer the data packet to the target node. Selfish nodes need to hide some important data and then only transmit normal data that try to misuse those data, so packet delivery rate is reduced. This normal method does not identify selfish nodes in the routing path. Proposed Incentive Sorted Path Selection Scheme (ISPSS), the progressively stable algorithm, enables the identification of such selfish nodes. The results confirm the enhancement in the lifetime of the network, the energy efficiency, and the delivery rates of the packets with reduced end-to-end delay.